Comparison of ground‐based and UAV a‐UHF artificial tracer mobility monitoring methods on a braided river. Issue 5 (13th February 2020) - Cassel, M.; Piégay, H.; Fantino, G.; Lejot, J.; Bultingaire, L.; Michel, K.; Perret, F.
Abstract: Radio frequency identification (RFID) technologies, which allow wireless detection of individual buried or immersed tracers, represent a step forward in sediment tracking, especially passive integrated transponders (PIT tags) that have been widely used. Despite their widespread adoption in the scientific community, they typically have low efficiency when deployed in river systems with active bedload transport or deep wet channels, attributed to their technical specifications. A recent evaluation of active ultra‐high frequency transponders (a‐UHF tags) assessed their larger detection range and provided a methodology for their geopositioning. In this study, we test five different survey methods (one including an unmanned aerial vehicle [UAV]) in a sediment tracking study, and compare them in terms of recovery rate, field effort, geopositioning error, and efficiency. We then tested the method on a larger reach following a Q5 flood and performed cross‐comparisons between active and passive RFIDs. The results confirmed that the a‐UHF RFID technology allowed rapid (1.5 h ha −1 ) survey of a large area (<34 ha) of emerged bars and shallow water channels with recovery of a high percentage of tracers (72%) that had travelled large distances (mean ≈ 1000 m; max ≈ 3400 m). Moreover, the tracers were identified with low geopositioning error (mean ≈ 7.1 m, ≤1% of their travel distance). We also showed that a UAV‐based survey was fast (0.38 h ha −1 ), efficient (recovery rate = 84%), and low error (mean ≈ 4.2 m). Thus, a‐UHF RFID technology permits the development of a variety of survey methods, depending on the study objectives and the human and financial resources available. This allows field efforts to be optimized by determining an appropriate balance between the high equipment cost of a‐UHF tracers and the resulting reduced survey costs. © 2019 John Wiley & Sons, Ltd. Abstract : a‐UHF tracers allow various survey methods to be used depending on human, material and financial ressources on one hand and prospection duration and location accuracy needed on the other hand.